A bridging immunogenicity assay for monoclonal antibody: case study with SHR-1222. (10th July 2018) - Zhang, Dan; Yang, Changyong; Chen, Xiaoyan; Li, Xiuli; Zhong, Dafang
Aim: SHR-1222 is a humanized monoclonal antibody targeted to soluble sclerostin. To support the preclinical study of SHR-1222 in cynomolgus monkeys, a method for the detection of anti-drug antibodies is required.Results: A bridging immunogenicity method for the detection of anti-SHR-1222 antibodies was developed and validated. In the method, minimal required dilution, normalization factor and confirmatory cut point were 1:20, 4.35 and 10.45%, respectively. The method was successfully applied to evaluate a multiple-dose toxicity study in monkeys.Conclusion: The proposed method allows for the detection of anti-SHR-1222 antibodies in preclinical studies and aids in the interpretation of pharmacokinetic changes in certain animals. The soluble targets interference on anti-drug antibody detection can be blocked or decreased by the therapeutic drug.